The role of self-concept in student engagement among Muslim students with family support as a mediating variable - Trisni Adelia; Hasanuddin Hasanuddin; Amanah Surbakti (INSPIRA: Indonesian Journal of Psychological Research, 2024)
The learning process is a crucial activity in enhancing the quality of learning outcomes, making the active role of students a significant factor. Family support influences student engagement in their learning at school. The research aims to examine the role of self-concept towards student engagement with family support as a mediating variable. This study utilizes a quantitative method involving data collection through scale completion. The sampling technique used is purposive sampling, where samples are selected based on specific characteristics. The results of this research indicate that self-concept plays a significant role in student engagement with family support as a mediator, with a Sobel test statistic of 2.202 > 1.96 and a two-tailed p-value of 0.02 < 0.05. This suggests that self-concept significantly and positively influences student engagement, and family support can mediate the emergence of student engagement behavior.